2022
DOI: 10.1029/2022jg006916
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Relative Drivers of Seasonal Evapotranspiration Across a Continental‐Scale Aridity Gradient

Abstract: Evapotranspiration (ET) is a significant ecosystem flux, governing the partitioning of energy at the land surface. Understanding the seasonal pattern and magnitude of ET is critical for anticipating a range of ecosystem impacts, including drought, heat‐wave events, and plant mortality. In this study, we identified the relative controls of seasonal variability in ET, and how these controls vary among ecosystems. We used overlapping AmeriFlux and PhenoCam time series at a daily timestep from 20 sites to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…The dominant hardwood vegetation composition at this site was sugar maple (Acer saccharum), basswood (Tilia americana L.), and green ash (Fraxinus pennsylvanica Marsh), mostly different from hardwood community found at RSWMA. However, a much higher effect of precipitation was reported in water-limited ecosystems as BHFs and seasonal cycles of canopy greenness in energy-limited ecosystems in higher latitudes using path analysis [31]. Similarly, in humid boreal regions, VPD and Rn were characterized as major drivers of sap-flow and thus transpiration during growing season as well as during drought [32].…”
Section: Discussionmentioning
confidence: 94%
“…The dominant hardwood vegetation composition at this site was sugar maple (Acer saccharum), basswood (Tilia americana L.), and green ash (Fraxinus pennsylvanica Marsh), mostly different from hardwood community found at RSWMA. However, a much higher effect of precipitation was reported in water-limited ecosystems as BHFs and seasonal cycles of canopy greenness in energy-limited ecosystems in higher latitudes using path analysis [31]. Similarly, in humid boreal regions, VPD and Rn were characterized as major drivers of sap-flow and thus transpiration during growing season as well as during drought [32].…”
Section: Discussionmentioning
confidence: 94%
“…The dominant hardwood vegetation composition at this site was sugar maple (Acer saccharum), basswood (Tilia americana L.), and green ash (Fraxinus pennsylvanica Marsh), mostly different from the hardwood community found in the RSWMA. However, a much higher effect of precipitation has been reported in water-limited ecosystems such as BHFs and seasonal cycles of canopy greenness in energy-limited ecosystems in higher latitudes using path analyses [31]. Similarly, in humid boreal regions, VPD and R n were characterized as major drivers of sap flow and thus transpiration during the growing season, as well as during drought [32].…”
Section: Discussionmentioning
confidence: 96%
“…Young et al. (2022) noted how the sensitivity of evapotranspiration across a continent as observed in the Ameriflux network of eddy covariance flux towers (Novick et al., 2018) scales primarily with plant lifecycle phenology in energy‐limited regions, while water limitation dominates elsewhere. Yan et al.…”
Section: A Scale For All Silosmentioning
confidence: 99%
“…Longer-term and distributed observations also allow for investigation of scale. Young et al (2022) noted how the sensitivity of evapotranspiration across a continent as observed in the Ameriflux network of eddy covariance flux towers (Novick et al, 2018) scales primarily with plant lifecycle phenology in energy-limited regions, while water limitation dominates elsewhere. Yan et al (2021) look further into spring plant phenology in China across a network of thousands of weather stations and find that large-scale atmospheric teleconnections such as the Atlantic Multidecadal Oscillation imprint themselves on the spring blooming times of individual organisms.…”
Section: A Scale For All Silosmentioning
confidence: 99%